Refugees, human rights, and realpolitik - Sharfman, Dafnah, author.
1 online resource.
Keywords: This book presents a multidimensional case study of international human rights in the immediate post-Second World War period, and the way in which complex refugee problems created by the war were often in direct competition with strategic interests and national sovereignty. The case study is the clandestine immigration of Jewish refugees from Italy to Palestine in 1945-1948, which was part of a British-Zionist conflict over Palestine, involving strategic and humanitarian attitudes. The result was a clear subjection of human rights considerations to strategic and political interests.